2012
DOI: 10.1371/journal.pone.0050229
|View full text |Cite
|
Sign up to set email alerts
|

SFRP2 and Slug Contribute to Cellular Resistance to Apoptosis in Hypertrophic Scars

Abstract: Hypertrophic scars (HS) are skin disorders which occur after wounding and thermal injury. Our previous studies have suggested that secreted frizzled-related protein 2 (SFRP2) is involved in HS formation and that the suppression of SFRP2 promotes apoptosis of hypertrophic scar fibroblasts (HSFBs). However, the mechanisms have not been clarified. Previous studies revealed that Slug expression inhibits cell apoptosis, in vitro and in vivo, and SFRP2 regulates the expression of Slug in cervical cancer cells. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
(56 reference statements)
2
9
0
Order By: Relevance
“…Another study showed that sFRP2 expression was significantly increased in hypertrophic tissues (Sun et al, 2011). It was suggested that sFRP2 acts during the formation of scars or keloids by contributing to collagen protein synthesis and suppressing fibroblast apoptosis (Chen et al, 2012). In this study, we demonstrated that sFRP2 is expressed both in the epidermis and dermis of human normal skin and that skin cells (melanocytes, keratinocytes, and fibroblasts) express sFRP2 constitutively.…”
Section: Discussionsupporting
confidence: 53%
“…Another study showed that sFRP2 expression was significantly increased in hypertrophic tissues (Sun et al, 2011). It was suggested that sFRP2 acts during the formation of scars or keloids by contributing to collagen protein synthesis and suppressing fibroblast apoptosis (Chen et al, 2012). In this study, we demonstrated that sFRP2 is expressed both in the epidermis and dermis of human normal skin and that skin cells (melanocytes, keratinocytes, and fibroblasts) express sFRP2 constitutively.…”
Section: Discussionsupporting
confidence: 53%
“…Investigations into additional signaling cascades could provide novel insights into the direct role of sFRP2 and metastatic mechanisms for osteosarcoma. Besides the aforementioned PI3K-Akt pathway, additional candidate mechanisms include the possibility that sFRP2 could positively regulate the expression of the stem cell transcription factor Slug [32], which is involved promoting the metastatic phenotypes of carcinomas [33]. Studies into if sFRP2 could alter the differentiation or stemness of osteosarcoma cells would also be interesting to investigate.…”
Section: Discussionmentioning
confidence: 99%
“…SFRP2 prevented cell death and local administration of exogenous SFRP2 reduced fibrosis and improved heart function . These antifibrotic of SFRP2 effects are not restricted to myocardiac tissue, but have also been implicated in wound repair of skin tissue . The reduced regenerative ability of aged HSCs have been attributed to accumulated replication stress, characterized by accumulation of the DNA damage response marker γH2A.X and activation of Cdc42, which, amongst others, reduces the polarized expression of the H4K16 acetylated marker .…”
Section: Discussionmentioning
confidence: 99%
“…Sfrp2 has been reported to be upregulated in situations of physiological stress. In particular, SFRP2 has been shown to regulate fibrotic responses in scarring of cardiac, and skin tissues and to play a major role in myocardial repair . SFRP2 is highly secreted by mineralized osteoblasts in the endosteal niche and SFRP2 has been suggested to inhibit differentiation of HSCs by enhancing self‐renewal .…”
Section: Introductionmentioning
confidence: 99%